Analisis Kelayakan Usaha Pengolahan Arum Manis UKM Dio di Desa Tegalreja, Kecamatan Banjarharjo, Kabupaten Brebes - Lili Nur Intan; Syariefful Ikhwan; Findhy Dwita Kumala; Roni; Dumadi (Journal of Accounting and Finance (JACFIN), 2019)
This research was conducted at UKM Arum Manis "Dio" in Tegalreja, Banjarharjo District, Brebes Regency. This study aims to analyze the feasibility of Small and Medium Enterprises (SMEs) Arum Manis "Dio". Data analysis methods that can be used in this study using cost and profit analysis formulas. Calculation of business feasibility, the formula used is Revenue Cost (R / C), Benefit Cost Ratio (B / C), and Return on Investment (ROI). The results showed that the average receipt at the Arum Manis "Dio" UKM was Rp. 96,000,000.00 per month with production costs incurred of Rp. 57,297,953.00 per month. The production cost consists of fixed costs of Rp. 520,953.00 per month and variable costs of Rp. 56,777,000.00 per month. From the results of data analysis, it was found that the profit obtained at the Arum Manis "Dio" UKM was Rp. 38,702,047.00 per month. Based on the calculation of business feasibility (R/C) Ratio is a comparison between receipts and total costs obtained value (R/C) Ratio 1.675 or 1.675 > 1. (B/C). Ratio is a comparison of profits with total production costs greater than zero, namely having a ratio of 0.675 or 0.675 > 0. Based on the comparison of profit and production capital, an ROI value of 57.5% can be drawn, so it can be concluded that the Arum Manis "Dio" SME can be said to be feasible and profitable.